Hortikultura Tanaman Bayam (Amaranthus Tricolor L.) dengan Pupuk Organik Cair Kulit Pisang - Malik Imam Muhajirin; Nur Asia; Nuryunita Nuryunita; Muarif Muarif; Merlin Merlin (Universitas Negeri Padang, 2020)
The purpose of this study was to observe the effect of plant height growth on spinach given the treatment of banana peel liquid fertilizer whether it can flourish or not. The approach in this research is a quantitative approach. This research is a completely randomized design (CRD), with 1 control and 4 treatments (50 ml, 100 ml, 150 ml, 200 ml) carried out with 6 repetitions. The treatment referred to here is that the plants are given fertilizer in different amounts in each treatment. The thing observed in this study is that 2 groups were randomly selected, one was given nothing (control) and the other group was treated. The effect of a treatment on the dependent variable will be tested by comparing the state of the dependent variable in the experimental group after being treated with the control group not treated.